2015
DOI: 10.1080/10934529.2015.1019811
|View full text |Cite
|
Sign up to set email alerts
|

Microwave oxidation treatment of sewage sludge

Abstract: Microwave-oxidation treatment of sewage sludge using various oxidants was studied. Two treatment schemes with a combination of hydrogen peroxide and ozone were examined: hydrogen peroxide and ozone were introduced into the sludge simultaneously, followed by microwave heating. The other involved the ozonation first, and then the resulting solution was subjected to microwave and hydrogen peroxide treatment. The set with ozonation followed by hydrogen peroxide plus microwave heating yielded higher soluble materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…More studies on the effect of temperature on phosphorus release are currently ongoing. Overall, the results from this and our earlier microwave studies re‐affirm that the process effectively disintegrated the solids, released nutrients and metals, and improved dewaterability and settling of the sludge. The resulting solution would be ideal for struvite crystallization and anaerobic digestion for methane production.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…More studies on the effect of temperature on phosphorus release are currently ongoing. Overall, the results from this and our earlier microwave studies re‐affirm that the process effectively disintegrated the solids, released nutrients and metals, and improved dewaterability and settling of the sludge. The resulting solution would be ideal for struvite crystallization and anaerobic digestion for methane production.…”
Section: Resultssupporting
confidence: 72%
“…In our earlier studies, the maximum phosphorus release occurred at 60 °C and orthophosphate was a major product . The MW/H 2 O 2 ‐AOP treatment of the sludge taken from the same MEBPR treatment system earlier (2 years ago) resulted in almost all of the soluble phosphorus being in the form of orthophosphate, and only a small fraction of polyphosphates being present in the microwave‐treated solutions . Based on our studies and others, it can be concluded that the release of phosphorus was dependent on its existent phosphorus forms in the sludge and EPS.…”
Section: Resultssupporting
confidence: 54%
“…Both RF-oxidation and MW/H 2 O 2 -AOP were very effective for cell disintegration and nutrient release from sewage sludge, as well as improving settleability, and reducing particle sizes. The treatment efficiency of RF-oxidation was comparable to MW/H 2 O 2 -AOP (Yin et al, 2007;Lo et al, 2015). RF-oxidation resulted in excellent settling compared to MW/H 2 O 2 -AOP.…”
Section: Rf and Mw Vs Conventional Heatingmentioning
confidence: 68%
“…Utilizing the unique features of dielectric heating, a thermalchemical treatment using a combination of microwave irradiation (MW) with hydrogen peroxide, namely, the microwave-enhanced advanced oxidation process (MW/H 2 O 2 -AOP) has been successful in destroying microbial cells and releasing nutrients from sewage sludge. It was used as a pretreatment process to produce a solution suitable for the subsequent struvite crystallization (magnesium ammonium phosphate) process for phosphorus recovery and/or anaerobic digestion to produce methane, as well as a carbon source for biological phosphorus removal process in an activated sludge system Yin et al, 2007;Chan et al, 2010;Lo et al, 2015). Unlike conventional heating methods, dielectric heat is generated via interaction of dielectric materials with electromagnetic radiation; either microwave spectrum or radiofrequency spectrum is used.…”
Section: Introductionmentioning
confidence: 99%
“…It is an energy efficient technology that is applicable in chemical reactions (Chen et al 2017). Several studies have focused on microwave pretreatment of fibrous raw materials (Manzoor et al 2013;Lo et al 2015). Microwave pretreatment allows a subsequent increase in enzyme activity (Chen et al 2017), but it requires a high investment.…”
Section: Microwave Pretreatmentmentioning
confidence: 99%